A SYSTEMATIC REVIEW ON NANO DRUG DELIVERY SYSTEM: SOLID LIPID NANOPARTICLES (SLN) - PHALAK, SWAPNIL D.; BODKE, VISHAL; YADAV, REENU; PANDAV, SATISH; RANAWARE, MALOJI (International Journal of Current Pharmaceutical Research, 2024)
Nanomedicine along with nano-delivery systems, are a young but fast-emerging science in which tiny materials are used as diagnostic tools or to deliver therapeutic drugs to specific targeted locations in a controlled manner. Nanotechnology has numerous advantages in the treatment of chronic human diseases through the site-specific and target-oriented delivery of precise medications. There have recently been several notable applications of nanomedicine (chemotherapeutic agents, biological agents, immunotherapeutic agents, and so on) in the treatment of various disorders. Efficient use of pricey medications and excipients, as well as cost savings in manufacturing Beneficial to patients, improved therapy, comfort, and the standard of living. Lipids have been proposed as an alternate carrier to circumvent the constraints of polymeric nanoparticles, notably for lipophilic medicines. Such small particles of lipid are known as solid lipid nanoparticles (SLNs), and they are gaining popularity among formulators all over the world. SLNs are colloidal carriers that were developed in the last decade as a replacement for traditional carriers. Lipid nanoparticles have caught the interest of researchers during the last two decades and have shown considerable therapeutic success since the first clinical approval of Doxil in 1995. Simultaneously, lipid nanoparticles have shown significant promise in conveying nucleic acid medications, as proven by the approval of two RNA treatments and an mRNA COVID-19 vaccination.